A mitochondrion-associated PPR protein, WBG1, regulates grain chalkiness in rice - Wu, Mingming; Cai, Maohong; Zhai, Rongrong; Ye, Jing; Zhu, Guofu; Yu, Faming; Ye, Shenghai; Zhang, Xiaoming (Frontiers in Plant Science, 2023)
Rice kernel quality has vital commercial value. Grain chalkiness deteriorates rice’s appearance and palatability. However, the molecular mechanisms that govern grain chalkiness remain unclear and may be regulated by many factors. In this study, we identified a stable hereditary mutant, white belly grain 1 (wbg1), which has a white belly in its mature grains. The grain filling rate of wbg1 was lower than that of the wild type across the whole filling period, and the starch granules in the chalky part were oval or round and loosely arranged. Map-based cloning showed that wbg1 was an allelic mutant of FLO10, which encodes a mitochondrion-targeted P-type pentatricopeptide repeat protein. Amino acid sequence analysis found that two PPR motifs present in the C-terminal of WBG1 were lost in wbg1. This deletion reduced the splicing efficiency of nad1 intron 1 to approximately 50% in wbg1, thereby partially reducing the activity of complex I and affecting ATP production in wbg1 grains. Furthermore, haplotype analysis showed that WBG1 was associated with grain width between indica and japonica rice varieties. These results suggested that WBG1 influences rice grain chalkiness and grain width by regulating the splicing efficiency of nad1 intron 1. This deepens understanding of the molecular mechanisms governing rice grain quality and provides theoretical support for molecular breeding to improve rice quality.